2016
DOI: 10.1038/srep26766
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged mitotic arrest induces a caspase-dependent DNA damage response at telomeres that determines cell survival

Abstract: A delay in the completion of metaphase induces a stress response that inhibits further cell proliferation or induces apoptosis. This response is thought to protect against genomic instability and is important for the effects of anti-mitotic cancer drugs. Here, we show that mitotic arrest induces a caspase-dependent DNA damage response (DDR) at telomeres in non-apoptotic cells. This pathway is under the control of Mcl-1 and other Bcl-2 family proteins and requires caspase-9, caspase-3/7 and the endonuclease CAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 25 publications
1
46
0
Order By: Relevance
“…Indeed, CAD‐induced DNA breaks that appear during prolonged mitotic arrest localize to telomeric regions. This telomeric localization likely reflects chromatin accessibility of mitotic cells, which would restrict CAD's activity . The specificity of CAD‐induced DNA breaks in an interphase cell is apparent during skeletal muscle differentiation, here the breaks appear restricted to euchromatic regions.…”
Section: Cad: Perspectivesmentioning
confidence: 98%
See 2 more Smart Citations
“…Indeed, CAD‐induced DNA breaks that appear during prolonged mitotic arrest localize to telomeric regions. This telomeric localization likely reflects chromatin accessibility of mitotic cells, which would restrict CAD's activity . The specificity of CAD‐induced DNA breaks in an interphase cell is apparent during skeletal muscle differentiation, here the breaks appear restricted to euchromatic regions.…”
Section: Cad: Perspectivesmentioning
confidence: 98%
“…Hain et al . recently explored the significance of the CAD‐induced telomeric DNA damage, and demonstrated this promoted a DNA‐PK‐dependent loss of TRF2 from the telomeres, further signaling dysfunction.…”
Section: Contribution Of Cad To Nonapoptotic Cell Fatesmentioning
confidence: 99%
See 1 more Smart Citation
“…For some cancer cell lines, e.g., U-2 OS, apoptosis after mitotic slippage is the major cell death response to anti-mitotic drug treatment and highly effective (~90% death after slippage) [18]. The key pro-apoptotic signal that activates cell death after slippage was identified to be DNA damage [22, 5459] (Fig. 3).…”
Section: Cell Death Response To Anti-mitotic Drugs In Cultured Cancermentioning
confidence: 99%
“…3). Several studies have shown that caspase activities, which were partially activated during prolonged mitotic arrest, engender DNA fragmentation in the post-slippage cells and thus induce p53-mediated DNA damage response [5659]. Our own results confirmed the involvement of DNA damage in post-slippage cell death and further illustrated that the degree of DNA damage induced by microtubule-targeting drugs, e.g., paclitaxel, is substantially higher than the spindle-targeting Kinesin-5 inhibitor [22].…”
Section: Cell Death Response To Anti-mitotic Drugs In Cultured Cancermentioning
confidence: 99%